Relationship Between Infrastructure And Economic Development Of Surabaya City - Riska Frida Pratiwi; Rossanto Dwi Handoyo (MediaTrend, 2021)
This study aims to identify the impact of infrastructure development on Economic Condition in Surabaya City. The variable used in this study are income per capita, dringking water distribution, sold energi (electricity) and condition of asphalted road. Data used in this paper is secondary data from 1993-2018. Model analysis used is time series regression analysis with selected models Error Correction Model (ECM) according to the econometric procedure. The result show that both dringking water distribution and sold electricity per capita have significant positif impact on per capita income in the long run,but in the short run all infratsructure indicatore no significant impact on development economics in Surabaya City.